Impact of humidity on chemical bonding, porosity and microstructure of 3D printed PLA - Abdul Hamid, Rahimah; Abdullah, Lokman; Sindam, Dorestey; Akmal, Suriati; Ito, Tatsuma (Penerbit Universiti Teknikal Malaysia Melaka, 2023)
Commonly used 3D printing material, such as polylactic acid (PLA), degrades when exposed to high temperatures and humidity. Moisture in the filament causes material degradation due to interactions with polymer molecules, particularly in hygroscopic filaments. This study aimed to investigate the impact of humidity on the chemical composition and porosity of 3D-printed PLA specimens. Four conditions were examined: a new PLA as a reference, used PLA stored in a vacuumed bag with 50g desiccant, used PLA stored without desiccant, and used PLA exposed to humidity for 48h, 96h, and 150h. Filament porosity was determined using the Archimedes Principle, while Fourier Transform Infrared Spectroscopy (FTIR) and Scanning Electron Microscope (SEM) were employed to analyze the chemical composition and structural changes, respectively. The findings revealed that humidity influences the chemical bonding of 3D-printed filaments, increasing the intensity of the O-H bond. More prolonged humidity exposure decreased density and increased porosity in the printed parts. Filaments stored with desiccant exhibited lower O-H bond intensity and porosity than those without desiccant. Additionally, prolonged humidity exposure, like 150h, caused more significant structural changes and larger surface morphology gaps, approximately 28.37%, than the control group, indicating lower density in the printed filaments. Therefore, the used filament must be stored properly to avoid moisture and produce porous and lower-strength 3D-printed parts.